School and the ideology of gender ideology - Lemos, Linovaldo Miranda (2017)
The paper aims at bringing elements to the understanding of the relationship between ideology and gender in order to contribute to the current debate on the so-called "gender ideology" and education. Although the arguments are generic and without solid scientific basis, critics of the discussion about gender in schools end up creating a mystification of reality and a vision of an imagined world that intends to be formally imposed without criticism. The purpose of the study is to debate the nature of this ideology and the impossibility of thinking about scientific and political neutrality in any sphere of our experiences, including schools.